Cultural Roots of Álvaro Cunqueiro’s “Magical Realism” (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
This work aims to study Álvaro Cunqueiro’s poetics of “magical realism”, through the analysis of some of his textual fragments. It is affirmed that his poetics takes root in the Cervantes tradition and, additionally, it reflects the interest of the Romantics for the medieval and popular sources of the marvelous. To comprehend Cunqueiro’s examples of magical realism we need to focus on the Cervantes pacto de ficción that, crossing the German Idealism and the French Surrealism, goes all the way though the Postmodern novel.
Keywords: XX Century Spanish Narrative; comparative literature; magical realism; postmodernism